2022
DOI: 10.1609/aaai.v36i11.21508
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Product Copywriting for E-commerce

Abstract: Product copywriting is a critical component of e-commerce recommendation platforms. It aims to attract users' interest and improve user experience by highlighting product characteristics with textual descriptions. In this paper, we report our experience deploying the proposed Automatic Product Copywriting Generation (APCG) system into the JD.com e-commerce product recommendation platform. It consists of two main components: 1) natural language generation, which is built from a transformer-pointer network and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…This was done to statistically account for variance in our outcome measures attributable to individual differences unrelated to people’s ad preferences (e.g., extraverts potentially giving higher scores on rating scales, or individual variation in the amount of money they can afford to spend when purchasing a smartphone). Specifically, we calculated the residuals for each outcome measure by regressing the targeted outcome (e.g., WTP for the phone advertised with the Openness ad) on the equivalent outcomes for the other traits (e.g., WTP for the phone advertised with the Conscientiousness, Extraversion and Agreeableness ads; see 43 for a similar approach). This allows us to isolate the unique variance in a participant’s preference that is unique to each specific ad (as opposed to the variance that is shared among all of them).…”
Section: Studies 3a–cmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done to statistically account for variance in our outcome measures attributable to individual differences unrelated to people’s ad preferences (e.g., extraverts potentially giving higher scores on rating scales, or individual variation in the amount of money they can afford to spend when purchasing a smartphone). Specifically, we calculated the residuals for each outcome measure by regressing the targeted outcome (e.g., WTP for the phone advertised with the Openness ad) on the equivalent outcomes for the other traits (e.g., WTP for the phone advertised with the Conscientiousness, Extraversion and Agreeableness ads; see 43 for a similar approach). This allows us to isolate the unique variance in a participant’s preference that is unique to each specific ad (as opposed to the variance that is shared among all of them).…”
Section: Studies 3a–cmentioning
confidence: 99%
“…For example, ad agencies have started to employ LLMs to create generic “ad copy” that can be published quickly 42 . Similarly, recent research suggests that automatically generated product descriptions in combination with human screening can result in improved click-through and conversion rates in e-commerce sites 43 . While these developments speak to the ability of LLMs to generate generic persuasive content, they do not offer any insights into (1) whether LLMs can create persuasive messages that are personalized to the needs and motivations of an individual and (2) whether doing so indeed makes these persuasive attempts more influential.…”
Section: Introductionmentioning
confidence: 98%
“…For example, ad agencies have started to employ LLMs to help create generic "ad copy" that can be published quickly (36). Similarly, recent research suggests that automatically generated product descriptions result in improved click-through rates and conversion rates on a large e-commerce website (37). While these developments speak to the ability of LLMs to generate simple yet relevant content, they do not offer any insights into whether LLMs can create messages that are personalized to and therefore more influential for specific psychological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Ravuru et al proposed combining VAE [12] and the PGN [8] and applying them to the task of paraphrasing [16]. Zhang et al combined the Transformer architecture with the PGN [17]. Zhang et al suggested that writing product copy is similar to abstract extraction.…”
Section: B Pointer Generator Network (Pgn)mentioning
confidence: 99%